THE EFFECT hCG (Human chorionic gonadotropin) TO OVULATION AND HATCHING OF FISH EGG OF SIBAN (Cyclocheilichtys apogon) - Desi Indriyani Manalu; Sukendi Sukendi; Nuraini Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted from April to Mei 2019 an the Hatchery and fish breeding Laboratory, Faculty of Fisheries and Marine, Riau University. The aims of this research was to know the effect of hCG (Human Chorionic Gonadotropin) pituitary gland injected with different dose on ovulation and survivaln rate of Siban (Cyclocheilithys apogon) and To find the best dose ot the pituitary gland to stimulate ovulation and survivaln rate of Siban (Cyclocheilithys apogon). The treatment used is as follows : PO Control using NaCL 0,9 %. P1 : hCG with dose 1000 IU/kg. P2 : hCG with dose 1200 IU/kg. P3 : hCG with dose 1400 IU/kg.The best result of the research is P2: Injection of hCG with dose 1200 IU/kg weight of test fish the with an average latent time 6 hours and 18minutes, amount eggs(items)/g 60 items,Fertilization Rate 78,36 % Hatching Rate 73,80 %, Survival Rate (SR) 74,79 % Water quality measurements range from: temperature 27-300C, DO 5,2-6,6 ppm, and pH 5-7. Keywords :Hormon hCG, Ovulation, Survival Rate, Cyclocheilichtys apogon